101 careers in social work - Ritter, Jessica A.; Vakalahi, Halaevalu F. Ofahengaue (Springer Publishing Company, 2015)
This guide to social work careers conforms to accreditation standards, core competencies, and licensing requirements, along with presenting opportunities for social workers resulting from health care reform and the Affordable Care Act. With a focus on the interdisciplinary nature of social work, the book describes both traditional careers and those that are off the beaten path in such arenas as forensic social work, entrepreneurship, working in political systems, international careers, and community planning. The authors also reflect upon the impact of the social and economic climate on the profession.--description provided by publisher.